Increased fragmentation of sleep–wake cycles in the 5XFAD mouse model of Alzheimer's disease. (2nd April 2015) - Sethi, M.; Joshi, S.S.; Webb, R.L.; Beckett, T.L.; Donohue, K.D.; Murphy, M.P.; O'Hara, B.F.; Duncan, M.J.
Highlights: AD patients have disturbed sleep, including increased sleep fragmentation. Sleep and wake patterns in 5XFAD mice, a model of AD, were examined. 5XFAD mice of both sexes were found to have reduced sleep bout lengths. Female 5XFAD were more severely affected, and had reduced total sleep as well. Sleep alterations in 5XFAD mice may be relevant to human AD sleep disturbances. Abstract: Sleep perturbations including fragmented sleep with frequent night-time awakenings and daytime naps are common in patients with Alzheimer's disease (AD), and these daily disruptions are a major factor for institutionalization. The objective of this study was to investigate if sleep–wake patterns are altered in 5XFAD mice, a well-characterized double transgenic mouse model of AD which exhibits an early onset of robust AD pathology and memory deficits. These mice have five distinct human mutations in two genes, the amyloid precursor protein (APP) and Presenilin1 (PS1) engineered into two transgenes driven by a neuron-specific promoter (Thy1), and thus develop severe amyloid deposition by 4 months of age. Age-matched (4–6.5 months old) male and female 5XFAD mice were monitored and compared to wild-type littermate controls for multiple sleep traits using a non-invasive, high throughput, automated piezoelectric system which detects breathing and gross body movements to characterize sleep and wake. Sleep–wake patterns were recorded continuously under baseline conditions (undisturbed) for 3 days and after sleep deprivation of 4 h, which in mice produces a significant sleep debt and challenge to sleep homeostasis. Under baseline conditions, 5XFAD mice exhibited shorter bout lengths (14% lower values for males and 26% for females) as compared to controls ( p < 0.001). In females, the 5XFAD mice also showed 12% less total sleep than WT ( p < 0.01). Bout length reductions were greater during the night (the active phase for mice) than during the day, which does not model the human condition of disrupted sleep at night (the inactive period). However, the overall decrease in bout length suggests increased fragmentation and disruption in sleep consolidation that may be relevant to human sleep. The 5XFAD mice may serve as a useful model for testing therapeutic strategies to improve sleep consolidation in AD patients.